Blockchain-Based TraditionalWeaving Certification and Elliptic Curve Digital Signature - Pradita Dwi Rahman; Heri Wijayanto; Royana Afwani; Wirarama Wesdawara; Ahmad Zafrullah Mardiansyah (Universitas Bumigora, 2024)
Traditional weaving in West Nusa Tenggara was essential to the region’s cultural heritage. Many local micro, small, and medium enterprises continued to practice traditional weaving using natural materials. However, the rise of synthetic materials threatened this tradition, making distinguishing between natural and synthetic woven fabrics difficult. This study aimed to develop a blockchain-based self-certification system to enhance traceability, security, and efficiency using Non-Fungible Tokens. The research method leveraged the Elliptic Curve Digital Signature Algorithm for user authentication and smart contracts to mint Non-Fungible Tokens, ensuring the authenticity and origin of each product.Each product’s metadata was signed with a digital signature that anyone could authenticate, and the outcome and the product metadata became a certificate. This study resulted in a web prototype with an easy-to-use interface that allowed artisans to create certificates and sell their registered works. This solution aimed to ensure the authenticity of traditional woven products by offering secure and transparent blockchain technology.